Efficacy and safety of insulin efsitora in type 2 diabetes: a meta-analysis of randomized controlled trials - Liu, Yang; Chen, Dingtao; He, Ke; Wei, Jichao; Liang, Miao; Han, Li; Li, Jingxin; Li, Xuejing; Wang, Xianying (Frontiers in Endocrinology, 2025)
ObjectiveThis meta-analysis aimed to evaluate the efficacy and safety profiles of insulin efsitora in the treatment of type 2 diabetes (T2D).MethodsWe conducted a comprehensive systematic search across PubMed, the Cochrane Library, and Embase from database inception through September 11, 2025. The study included randomized controlled trials (RCTs) that directly compared insulin efsitora with once daily basal insulin in T2D patients. Primary outcomes assessed were changes in hemoglobin A1c (HbA1c) and body weight. Methodological quality and risk of bias were evaluated using the Cochrane Quality Assessment Tool. Data synthesis was performed using random-effects models to calculate risk ratios (RR) and mean differences (MD).ResultsThe meta-analysis incorporated six RCTs involving 4116 participants. Our findings revealed no statistically significant difference in HbA1c reduction between insulin efsitora and once daily basal insulins (MD: -0.04%; 95% CI: -0.10% to 0.02%; p = 0.78). Other outcomes, including change in body weight, body mass index changes, proportion of patients achieving HbA1c < 7%, change in fasting plasma glucose, and various hypoglycemia events (level 1, level 2, and level 3), as well as adverse events and serious adverse events, showed comparable results between the two treatments. Notably, insulin efsitora demonstrated superior performance in total daily insulin dose and time in range (70-180 mg/dL).ConclusionsInsulin efsitora demonstrates comparable efficacy and safety to once daily basal insulins in the management of T2D. However, given the limited number of RCTs available in the current evidence base, further large-scale clinical trials are warranted to validate these findings and establish more definitive conclusions.